2009
DOI: 10.1519/jsc.0b013e3181b3dd7a
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Immunoglobulin A Response to a Match in Top-Level Brazilian Soccer Players

Abstract: It has been suggested that several parameters of mucosal immunity, including salivary immunoglobulin A (s-IgA), are affected by heavy exercise either in field sports or in the laboratory environment. Few observations have been made during a true sporting environment, particularly in professional soccer. We tested the hypothesis that salivary IgA levels will be decreased after a 70-minute regulation in a top-level professional soccer friendly match. Saliva samples from 24 male professional soccer players collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 21 publications
4
34
1
10
Order By: Relevance
“…In our previous study with top-level soccer player considering distinct expressions of salivary immunoglobulin A responses after a match, this large variability was also emerged (Moreira et al 2009). This fact motivated us to investigate the salivary cortisol response after a competitive training match in a cohort of top-level professional soccer players.…”
Section: Discussionmentioning
confidence: 74%
“…In our previous study with top-level soccer player considering distinct expressions of salivary immunoglobulin A responses after a match, this large variability was also emerged (Moreira et al 2009). This fact motivated us to investigate the salivary cortisol response after a competitive training match in a cohort of top-level professional soccer players.…”
Section: Discussionmentioning
confidence: 74%
“…However, it has been suggested that correction with total protein is inappropriate and misleading [52]. Studies have identified no change in sIgA or flow rate following intense exercise, but an increase in total salivary protein, which indicates an evaporative loss of saliva when breathing through the mouth during exercise [53,54]. 4.…”
Section: Correction Of Measurements For Salivary Flow Ratementioning
confidence: 99%
“…Immediately after collection, the saliva samples were frozen and stored at 280°C until assaying for sC and sIgA concentrations. The sIgA and sC concentrations were measured in duplicate as done in previous studies (13,14). Briefly, sIgA concentration was measured by an enzyme-linked immunosorbent assay (ELISA, SIgA EIA kit, Alpco Diagnostics, Salem, MA, USA).…”
Section: Saliva Sampling and Analysismentioning
confidence: 99%